Income Maintenance in Old Age: What Can be Learned from Cross-National Comparisons - Timothy M. Smeeding (Luxembourg Income Study (LIS), 2001)
The purpose of this paper is to review the recent evidence on the antipoverty effectiveness and other characteristics of income maintenance systems for the elderly in the rich nations of the world. As we move toward Social Security reform in the United States, we do so knowing that a comparatively high fraction of our older population experience, income poverty compared to their counterparts in other nations. Strategies to reduce the future Social Security deficit need to take into account the way that program changes affect poverty and benefit adequacy as well as fiscal soundness. Other nations offer approaches which would help us to achieve lower poverty rates while also providing fiscally responsible solutions to the future public costs of an aging society through reforms to the Social Security system.
Keywords: 330; Altersvorsorge; Rentenreform; Armut; Industrieländer; USA